Structural, optical and morphological properties of TiO2/Ag/TiO2 multilayer films - Hasan, M.M.; Haseeb, A.S. Md. Abdul; Saidur, Rahman; Masjuki, Haji Hassan; Johan, Mohd Rafie (American Institute of Physics, 2009)
In this investigation, TiO 2/Ag/TiO 2 multilayer-films were deposited on microscope glass slides with varying individual layer thicknesses by radio-frequency reactive magnetron sputtering. Prior to multilayer development, single layers of Ag and TiO 2 were deposited and characterized. All the films were prepared at a moderately high pressure at room temperature. It was found that single layer of TiO 2 showed anatase polycrystalline structure. It also exhibited high visible transmittance of above 80 and higher refractive index of 2.31 at a wavelength of 550 nm. The indirect optical band gap of the TiO 2 films was estimated as 3.39 eV. The Ag single layer films were found to be crystalline with a very high reflectance for IR (Infra-red) light. Finally, the multilayers have been deposited and characterized by X-ray diffraction, UV-visible-IR spectrophotometry, scanning electron microscopy and profilometry.